The Consequences of the Value-Added Tax on Inequality - Kaisa Alavuotunki; Mika Haapanen; Jukka Pirttilä (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper examines the impact of the introduction of the value-added tax on inequality and government revenues using newly released macro data. We present both conventional county fixed effect regressions and instrumental variable analyses, where VAT adoption is instrumented using the previous values of neighbouring countries VAT systems as an instrument. The results reveal – in contrast to earlier work – that the revenue consequences of the VAT have not been positive. The results indicate that income-based inequality has increased due to the VAT adoption, whereas consumption inequality has remained unaffected.
Keywords: H23; O23; 330; tax policy; value-added tax; inequality; developing countries